Conflict In-Laws and Son-in-Law in Merariq Tradition - Adhiningsih, Aliya Dwi Citra; Nedyasari, Dhiny; Suteja, Deby (Ilomata International Journal of Social Science, 2024)
This research explores the impact of the Merariq practice on interpersonal communication within families in Nyurlembang Village, West Lombok Regency, West Nusa Tenggara. Utilizing a qualitative approach and employing a phenomenological case study methodology, this research engages with five merariq wives and one respective parents who is unaware of the kidnapping process. Data collection is conducted through semi-structured interviews and analyzed using Nvivo. The findings indicate that Merariq creates conflict, especially in the communication between prospective spouses and parents. In conclusion, an educational approach, open dialogue, and socialization programs are essential to raise awareness, improve interpersonal communication, and prevent tension in family relationships. The practical implications involve real efforts to enhance harmony within the cultural context of Merariq.